Comprehensive cardiac pacemaker information system: basis for a regional follow-up NETWORK. - Hanson JS; Grant ME (Pacing & Clinical Electrophysiology, 1978)
The capabilities of a mini-computer-oriented permanent pacemaker information system are described. Extensive patient and pacer functional data. are maintained in readily accessible files which may be displayed on a CRT terminal or printed out. Selective sorting of stored information may be accomplished according to any desired set of inclusive or exclusive criteria. Intelligent, comprehensive patient follow-up has been greatly facilitated through application of the system. In view of the rapidly expanding pacemaker population, it is suggested that cooperative regional networks operating with come parable information storage and retrieval structures will provide the only means for adequate patient surveillance and compilation of necessary pacemaker data.